Investigating the risks of late preterm and term neonatal morbidity across clinical subtypes of intrahepatic cholestasis of pregnancy - Tang, Wei-Zhen; Zhao, Yi-Fan; Wang, Lan; Cai, Qin-Yu; Xu, Wei-Ze; Wen, Li; Chen, Xue-Bing; Sheng, Ting-He; Fan, Tian-Qi; Liu, Tai-Hang; Li, Rong; Liu, Shang-Jing (Frontiers in Medicine, 2025)
BackgroundThis investigation assesses the perinatal risks associated with different clinical subtypes of intrahepatic cholestasis of pregnancy (ICP) based on clinical symptomatology, with the goal of informing optimal delivery timing for each specific ICP subtype.Study designThe retrospective study encompassed 2,057 singleton pregnancies with ICP, categorized into the single-symptomatic (ICP-S) and the multisymptomatic (ICP-M) groups. The ICP-M group was further subdivided based on symptom combinations: elevated TBA with elevated transaminases (ICP-MT), elevated TBA with pruritus (ICP-MP), and combined elevations with pruritus (ICP-MB). The investigation included an assessment of baseline characteristics, a comparison of perinatal outcomes between the ICP-S and ICP-M groups, an evaluation of the impact of ursodeoxycholic acid and second-line treatments, and the analysis of severe adverse neonatal outcomes by clinical classification and gestational age through the logistic regression and restricted cubic spline methods.ResultsBaseline characteristics suggested in vitro fertilization (IVF) and nullipara as more prevalent in the ICP-M, which also had an earlier diagnosis of ICP than in the ICP-S. In addition, the ICP-M exhibited higher liver function and blood glucose levels. The ICP-M was significantly associated with increased risks of gestational diabetes mellitus (GDM) (OR 1.57), preterm birth (OR 1.92), low-birth-weight infant (OR 1.81), and neonatal intensive care unit (NICU) admissions (OR 1.48) than the ICP-S. Among the ICP-M subgroups, the ICP-Mp exhibited the highest risk of adverse outcomes. Ursodeoxycholic acid (UDCA) treatment was found to be beneficial in reducing the risk of preterm birth, particularly in the ICP-M. The study also highlighted that late preterm or post-term delivery in the ICP-M patients exacerbates NICU risk.ConclusionWomen with ICP-M experience elevated perinatal risks, including a higher risk of coexisting GDM, as well as increased risks of preterm birth and NICU admissions. Personalized clinical management, optimizing delivery timing based on clinical subtypes, and providing UDCA to improve neonatal outcomes during pregnancy are important measures worthy of attention.